Heart Rate Reduction With Ivabradine Protects Against Left Ventricular Remodeling by Attenuating Infarct Expansion and Preserving Remote‐Zone Contractile Function and Synchrony in a Mouse Model of Reperfused Myocardial Infarction. Issue 4 (April 2016) - O'Connor, Daniel M.; Smith, Robert S.; Piras, Bryan A.; Beyers, Ronald J.; Lin, Dan; Hossack, John A.; French, Brent A.
Abstract : Background: Ivabradine selectively inhibits the pacemaker current of the sinoatrial node, slowing heart rate. Few studies have examined the effects of ivabradine on the mechanical properties of the heart after reperfused myocardial infarction (MI). Advances in ultrasound speckle‐tracking allow strain analyses to be performed in small‐animal models, enabling the assessment of regional mechanical function. Methods and Results: After 1 hour of coronary occlusion followed by reperfusion, mice received 10 mg/kg per day of ivabradine dissolved in drinking water (n=10), or were treated as infarcted controls (n=9). Three‐dimensional high‐frequency echocardiography was performed at baseline and at days 2, 7, 14, and 28 post‐MI. Speckle‐tracking software was used to calculate intramural longitudinal myocardial strain (Ell ) and strain rate. Standard deviation time to peak radial strain (SD Tpeak Err ) and temporal uniformity of strain were calculated from short‐axis cines acquired in the left ventricular remote zone. Ivabradine reduced heart rate by 8% to 16% over the course of 28 days compared to controls ( P <0.001). On day 28 post–MI, the ivabradine group was found to have significantly smaller end‐systolic volumes, greater ejection fraction, reduced wall thinning, and greater peak Ell and Ell rate in the remote zone, as well as globally. Temporal uniformity of strain and SD Tpeak Err were significantly smaller in the ivabradine‐treated group by day 28 ( P <0.05). Conclusions: High‐frequency ultrasound speckle‐tracking demonstrated decreased left ventricular remodeling and dyssynchrony, as well as improved mechanical performance in remote myocardium after heart rate reduction with ivabradine.